2011
DOI: 10.1007/s10560-011-0227-z
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Effects of Long-Term Bombardment Among Israeli Adolescents: The Role of Gender and Social Environment

Abstract: The effects of living under long-term bombardment were studied among 1,004 adolescent students in Israel. The study was based on the theoretical framework of the conservation of resources and examined differences between boys and girls who live in high and low socioeconomic environments. The findings revealed that students from a low socioeconomic status (SES) and girls present more negative symptoms than high SES students and boys, while concomitantly exhibiting greater posttraumatic growth. The contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
3
9
0
Order By: Relevance
“…In accordance with other studies, female adolescents in our sample reported more PTSD symptoms, higher levels of distress, and less life satisfaction than did males (e.g., Canetti et al, 1997; Galea et al, 2002; T. Lavi et al, 2013; Roussos et al, 2005; Yablon, Itzhaky, & Pagorek-Eshel, 2011). Also in keeping with earlier findings (Canetti et al, 1997; Pedersen, 1994), females in our sample perceived their mothers as more caring than the males.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with other studies, female adolescents in our sample reported more PTSD symptoms, higher levels of distress, and less life satisfaction than did males (e.g., Canetti et al, 1997; Galea et al, 2002; T. Lavi et al, 2013; Roussos et al, 2005; Yablon, Itzhaky, & Pagorek-Eshel, 2011). Also in keeping with earlier findings (Canetti et al, 1997; Pedersen, 1994), females in our sample perceived their mothers as more caring than the males.…”
Section: Discussionsupporting
confidence: 93%
“…Lavi et al, 2013;Roussos et al, 2005;Yablon, Itzhaky, & Pagorek-Eshel, 2011). Also in keeping with earlier findings (Canetti et al, 1997;Pedersen, 1994), females in our sample perceived their mothers as more caring than the males.…”
Section: Discussionsupporting
confidence: 91%
“…Other Israel based studies have examined trauma impact on emotional disorders such as anxiety and depression (Baker and Shalhoub-Kevorkian 1999;Cohen and Eid 2007;Farbstein et al 2010), aggressive behaviour (Al-Krenawi, Graham, and Kanat-Maymon 2009;R. Pat-Horenczyk, Abramovitz, et al 2007;Yablon, Itzhaky, and Pagorek-Eshel 2011;Klodnick et al 2014;Marie-Alsana, Haj-Yahia, and Greenbaum 2006). Few have investigated behavior disorders such as conduct or attention deficit/hyperactive disorder (Farbstein et al 2010).…”
Section: Israel Contextmentioning
confidence: 99%
“…Pat-Horenczyk et al 2009). (Yablon, Itzhaky, & Pagorek-Eshel, 2011) despite the Israeli Arab population experiencing greater political, economic and social challenges (Al-Krenawi, Graham, and Kanat-Maymon 2009;Ron 2014).…”
Section: Israel Contextmentioning
confidence: 99%
“…In a similar vein, Yablon et al (2011) examined the impacts of long-term bombardment among 1004 adolescents in Israel. Using the framework of the conservation of resources, the study investigated differences between boys and girls from high and low socioeconomic areas.…”
Section: Self-efficacy Among Adolescentsmentioning
confidence: 99%